Effects of diets containing vegetable oil on expression of genes involved in highly unsaturated fatty acid biosynthesis in liver of Atlantic salmon (Salmo salar) - Zheng, Xiaozhong; Tocher, Douglas R; Dickson, Cathryn; Bell, J Gordon; Teale, Alan J (Aquaculture, 2004)
Fish are an important dietary source of the long-chain C20 and C22 highly unsaturated fatty acids (HUFA), arachidonate (20:4n-6), eicosapentaenoate (20:5n-3) and docosahexaenoate (22:6n-3), that are crucial to the health of higher vertebrates and that can be beneficial in human diets. Δ5 and Δ6 fatty acid desaturases, and fatty acid elongases are critical enzymes in the biosynthetic pathways of HUFA from shorter chain C18 polyunsaturated fatty acids (PUFA) such as linoleic (18:2n-6) and α-linolenic (18:3n-3) acids. Recently, full-length cDNAs for fatty acid desaturase and elongase enzymes have been cloned from Atlantic salmon. Functional characterisation of the desaturase revealed n-3 Δ5 desaturase activity, whereas the elongase had broad substrate specificity for PUFA with a range of chain lengths from C18 to C22. The study described here was primarily focused on the nutritional regulation of genes involved in the HUFA biosynthetic pathway in Atlantic salmon. A feeding trial was performed whereby salmon smolts in seawater pens were fed for 40 weeks on five different diets. The diets consisted of a control diet containing fish oil (FO) and four diets in which the FO was replaced in a graded manner by linseed oil (LO). Specifically, in terms of added oils, the five diets were 100% FO (FO), 100%LO (LO100) and FO/LO in ratios of 3:1 (LO25), 1:1 (LO50) and 1:3 (LO75). Fish were sampled at 20 and 40 weeks, and samples of liver were collected for lipid analyses and total RNA extraction. Hepatocytes were also prepared and the activity of the HUFA biosynthetic pathway determined. Expression of fatty acid desaturase and elongase genes was determined by quantitative real time PCR and the ratio of the copy number of the targeted gene against that of β-actin was calculated. The results showed that after 20 weeks of feeding, desaturase and elongase gene expression in liver was increased in a graded manner by increasing dietary LO. Expression of both genes was positively and negatively correlated with dietary 18:3n-3 and n-3 ...